KEUTAMAAN ILMU SEBAGAI LANDASAN PENDIDIKAN NILAI DALAM PERSPEKTIF HADIS NABI - Mirza Mahbub Wijaya (JP : JURNAL PENDIDIKAN, 2021)
Abstrac; In this study, the researcher attempted to explore fundamentally the value education contained in one of the hadiths of the Prophet narrated by at-Tirmidhi. This research is very important because it tries to dig up an interpretation of one of the popular Hadiths. This research is a library research type. Armed with literature data, the researchers then analyzed using the hermeneutic method. So, the researchers got five points of discussion. 1) Religious spiritual values, hat not limited in material world but also in eschatology. 2) The value of hard work, a value that a person possesses the enthusiasm to strive to achieve goals. 3) Istiqomah value, which means being unchanging, disciplined, and loyal in carrying out obedience to God and other rules 4) Exemplary Value, has the meaning of a case or something worthy of being imitated 5) The value of love of knowledge, which means passion to get knowledge to build the quality of human self, civilization, and eternal happiness both physically and mentally.Keywords: Islamic Education, Values Education, The Virtue of Science